2021
DOI: 10.21203/rs.3.rs-1179000/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

S-palmitoylation and sterol interactions mediate antiviral specificity of IFITM isoforms

Abstract: Interferon-induced transmembrane proteins (IFITM1, 2 and 3) are important antiviral proteins that are active against many viruses, including influenza A virus (IAV), dengue virus (DENV), Ebola virus (EBOV), Zika virus (ZIKV) and severe acute respiratory syndrome coronavirus (SARS-CoV). IFITMs exhibit isoform-specific activity, but their distinct mechanisms of action and regulation are unclear. Since S-palmitoylation and cholesterol homeostasis are crucial for viral infections, we investigated IFITM interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 69 publications
(62 reference statements)
2
16
0
Order By: Relevance
“…Furthermore, they proposed that a region of IFITM3 proximal to the transmembrane domain (TMD) encodes a putative CARC consisting of 104 K CLNI W ALI L 113 (underlined residues indicate the basic, aromatic, and aliphatic residues that define a putative cholesterol binding region, as seen in certain G-protein coupled receptors (Fantini and Barrantes, 2013)). Deletion of this region led to partial loss of cholesterol analog binding, suggesting that this region of IFITM3 protein contributes to cholesterol binding in vivo (Das et al, 2021). Therefore, we tested whether a peptide overlapping with 104 K CLNI W ALI L 113 conferred potential for direct cholesterol binding in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they proposed that a region of IFITM3 proximal to the transmembrane domain (TMD) encodes a putative CARC consisting of 104 K CLNI W ALI L 113 (underlined residues indicate the basic, aromatic, and aliphatic residues that define a putative cholesterol binding region, as seen in certain G-protein coupled receptors (Fantini and Barrantes, 2013)). Deletion of this region led to partial loss of cholesterol analog binding, suggesting that this region of IFITM3 protein contributes to cholesterol binding in vivo (Das et al, 2021). Therefore, we tested whether a peptide overlapping with 104 K CLNI W ALI L 113 conferred potential for direct cholesterol binding in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we suspect that engagement of cholesterol by the AH of IFITM3 similarly increases its penetrative depth and positioning within membranes and confers it with a greater capacity to stiffen and bend membranes during the virus-cell membrane fusion reaction. In fact, in the aforementioned pre-print posted during preparation of this manuscript, the authors used molecular simulations to suggest that cholesterol affects the positioning of the AH of IFITM3 in membranes (Das et al, 2021). Therefore, our description of the cholesterol binding potential of the AH likely contributes to this atomic-level observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CARC domain lies on N-terminus of IFITM3, a conserved motif that mediates direct interaction between this transmembrane protein and cholesterol. Further study suggested that the CARCΔ construct of IFITM3 showed a significant loss of antiviral activity against IAV and SARS-CoV-2 infection compared with IFITM3 WT ( 87 ). In addition, cholesterol can facilitate the negative membrane curvature induced by IFITM3 resulting in increased lipid order and membrane stiffness ( 75 ).…”
Section: Antiviral Activities Of Interferon-induced Transmembrane Pro...mentioning
confidence: 99%
“…High levels of S-palmitoylation enhanced IFITM3 interactions with cholesterol and inhibited viruses like IAV and SARS-CoV2. While with lower levels of S-palmitoylation and fewer interactions with cholesterol, IFITM2 showed more efficient anti-EBOV activity, indicating that S-palmitoylation may inhibit cholesterol-dependent viruses by regulating the interaction between IFITM3 and cholesterol ( 87 ).…”
Section: Mechanism Of S-palmitoylation To Regulate the Antiviral Capa...mentioning
confidence: 99%